Don't listen to the guy above talking about integration. Integration is NOT the reversal of differentiation. That would be the anti-derivative. Integrals and anti-derivatives are NOT the same thing. But they are connected by the Fundamental Theorem of Calculus.

If a function f(x) has an anti-derivative F(x), the area under the curve from a to b is equal to F(b)-F(a).

This is integration defined.

This is integration defined.

by MIT 2010 January 14, 2007

The process of searching a building for an empty bathroom. A successful bowl search typically relieves the frustration of uncomftorably defecating around others, although in less frequent cases the desire to urinate alone is a factor. Bowl searching can be done anywhere although it is most prevelant on college campuses.

"In college I did a lot of bowl searching."

"Sam went to the bathroom like 20 minutes ago. Jeez, what's taking so long?"

"He's probably bowl searching."

"Sam went to the bathroom like 20 minutes ago. Jeez, what's taking so long?"

"He's probably bowl searching."

by A bowl searcher June 06, 2011

the reverse process of differentiaton

we know that, for example if f(x) = 2x^3 - 5x^2 + 3x -7

then f'(x) = 6x^2 - 10x + 3

This process can be reversed.

In general, y = x^n -> dy/dx = nx^(n-1)

So, reversing this process, it would seem that dy/dx = x^m -> y = (1/(m+1))x^(m+1)

The general process of finding a function from its derivative is known as interation.

we know that, for example if f(x) = 2x^3 - 5x^2 + 3x -7

then f'(x) = 6x^2 - 10x + 3

This process can be reversed.

In general, y = x^n -> dy/dx = nx^(n-1)

So, reversing this process, it would seem that dy/dx = x^m -> y = (1/(m+1))x^(m+1)

The general process of finding a function from its derivative is known as interation.

Given that dy/dx = 12x^2 + 4x - 5, find an expression for y.

y = 12((x^3)/3) + 4((x^2)/2) - 5((x^1)/1)

It would seem that

y=4x^3 + 2x^2 - 5x

but that is not quite the complete answer

Whenever you differentiate a constant you get zero,

e.g. y = 7 dy/dx = 0

and so the expression for y above could have any constant on the end and still satisfy dy/dx = 12x^2 + 4x - 5

The answer to this example is therefore

y= 4x^3 + 2x^2 - 5x + c, where c is a constant.

y = 12((x^3)/3) + 4((x^2)/2) - 5((x^1)/1)

It would seem that

y=4x^3 + 2x^2 - 5x

but that is not quite the complete answer

Whenever you differentiate a constant you get zero,

e.g. y = 7 dy/dx = 0

and so the expression for y above could have any constant on the end and still satisfy dy/dx = 12x^2 + 4x - 5

The answer to this example is therefore

y= 4x^3 + 2x^2 - 5x + c, where c is a constant.

by hotgirl69xxx December 22, 2004

by Atticus Coon March 07, 2005

#### Feb 24 trending

- 1. Watermelon Sugar
- 2. Ghetto Spread
- 3. Girls who eat carrots
- 4. sorority squat
- 5. Durk
- 6. Momala
- 7. knocking
- 8. Dog shot
- 9. sputnik
- 10. guvy
- 11. knockin'
- 12. nuke the fridge
- 13. obnoxion
- 14. Eee-o eleven
- 15. edward 40 hands
- 16. heels up
- 17. columbus
- 18. ain't got
- 19. UrbDic
- 20. yak shaving
- 21. Rush B Cyka Blyat
- 22. Pimp Nails
- 23. Backpedaling
- 24. Anol
- 25. got that
- 26. by the way
- 27. Wetter than an otter's pocket
- 28. soy face
- 29. TSIF
- 30. georgia rose